Risk Factors Affecting Respiratory Symptoms and Impaired Lung Function of Palm Oil Mill Workers in the District of Kandis - Surya Hajar Fitria Dana; Indi Esha; Faisal Yunus; Adrianison Adrianison; Azizman Saad; Ridha Restilla (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Air pollution that exposed to human have been a problem all over the world and caused a variety of lung disease. Gases and particles emitted from industry including sulfur oxide, nitrogen oxide, and particulate matter may lead to decreasing lung function. Sulfur dioxide is one of the highest causes of air pollution at the highest level. Workers exposure to gases were vulnerable to respiratory function abnormality. Methods: A study on the effect of risk factors and sulfur dioxide exposure on lung function of palm oil workers in the district of Kandis was carried out in December 2019–January 2020. The research aim at describing sulfur dioxide air ambient in palm oil mill as well as respiratory state of palm oil workers and analyzing sulfur dioxide exposure and lung function relationship. Result: The result showed that sulfur dioxide concentration in outdoor 25.7 µg/Nm3 and indoor 20.6 µg/Nm3. The result of spirometry showed obstruction in 13% of the workers. Breathlessness and productive cough are the most common symptoms. Several factors that correlated with lung function namely as personal protective equipment (p=0.001), length of working (p=0.003), and smoking habit (p=0.004). From multivariate analysis, personal protective equipment has a significant correlation with lung function (p=0.038). Conclusion: Increasing the concentration of sulfur dioxide may cause decreased of lung function but other factor like personal protective equipment showed a significant correlation with lung function.